2012
DOI: 10.1155/2012/878241
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Urogenital Infections in Pregnant Women Experiencing Preterm and Full-Term Labor

Abstract: Urogenital infections are extremely prevalent during pregnancy and are an important cause of premature labor. However, the prevalence of urogenital infections during childbirth is not well known.Objective. Identify urogenital infections present at the beginning of labor in both full-term and preterm pregnancies.Study Design. Ninety-four women were admitted to the inpatient maternity clinic of the Federal University of Rio Grande do Norte (UFRN). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 16 publications
4
50
3
7
Order By: Relevance
“…CG et al have proved that lower genital tract infections are very common among apparently healthy looking pregnant women with an overall prevalence of 40-54%. 14 The prevalence of BV during pregnancy has been reported as 20-30% in various studies. The present study estimated the prevalence of BV based on positive Amsel's criteria among preterm labour group as 30% and among term labour as 4% which coincides with the findings of Mittal et al and Svare et al 15,16 Findings in the study of Hiller and coworkers and Subtil et al demonstrated the increased association of preterm delivery with bacterial vaginosis which is also demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…CG et al have proved that lower genital tract infections are very common among apparently healthy looking pregnant women with an overall prevalence of 40-54%. 14 The prevalence of BV during pregnancy has been reported as 20-30% in various studies. The present study estimated the prevalence of BV based on positive Amsel's criteria among preterm labour group as 30% and among term labour as 4% which coincides with the findings of Mittal et al and Svare et al 15,16 Findings in the study of Hiller and coworkers and Subtil et al demonstrated the increased association of preterm delivery with bacterial vaginosis which is also demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that increase the risk of urinary tract infections in pregnant women include increased age, number of intercourses per week, number of childbirths, recessive sickle cell anemia, diabetes, immunodeficiency and urinary tract abnormalities 13,14 . The probability of urinary tract infection initiated around the sixth week and reaches the maximum during 22-24 weeks of gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…The probability of urinary tract infection initiated around the sixth week and reaches the maximum during 22-24 weeks of gestational age. The increased probability of infection in pregnant women is most likely due to increased bladder volume, its expansion and expanded ureter 13,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Microbial infections of the vagina (vaginosis and vaginitis) among pregnant women are serious problems because they can lead to serious medical complications such as preterm labor, amniotic fluid infection, premature rupture of the fetal membranes, and low birth weight of the neonate [1], leading to high prenatal mortality [2]. However, proper identification and treatment will reduce the risk of preterm birth and its consequences [3].…”
Section: Introductionmentioning
confidence: 99%
“…The vagina could be infected by a variety of pathogens including bacteria, fungi, viruses, and parasites [1,2]. Bacterial vaginosis (BV) is the most frequent vaginal infection, characterized by the replacement of Lactobacillus species of normal vaginal flora by the excessive growth of a mixture of microorganisms including Gardnerella vaginalis, Bacteroides species, genital mycoplasma, and fastidious anaerobic bacteria [4].…”
Section: Introductionmentioning
confidence: 99%